Seeing the forest and the trees: Examining the impact of aggregate measures of recidivism on meta-analytic conclusions of intervention effects - Bouchard, Jessica (Criminology & criminal justice, 2024)
Recidivism is a multidimensional construct that is operationalized in a variety of ways. We explored the impact of using aggregated measures of recidivism (i.e. multiple measures combined) versus disaggregated measures (i.e. defined specifically as parole violation, arrest, conviction, incarceration) in meta-analytic analyses of correctional intervention effectiveness. Using a sample of 20 meta-analyses, we compared within-study findings between aggregated and disaggregated measures. Over half (60%) of the studies differed with respect to the statistical significance of their aggregated versus disaggregated findings, suggesting that aggregated measures of recidivism may give an incomplete picture of treatment effectiveness. Disaggregating measures of recidivism in meta-analysis is recommended for a comprehensive assessment of the impacts of intervention approaches. Policy implications are discussed.